2020
DOI: 10.3390/antibiotics9030100
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Gold Nanoparticles as Potent Antibacterial and Antibiofilm Nano-Antibiotics against Pseudomonas aeruginosa

Abstract: Plant-based synthesis of eco-friendly nanoparticles has widespread applications in many fields, including medicine. Biofilm—a shield for pathogenic microorganisms—once formed, is difficult to destroy with antibiotics, making the pathogen resistant. Here, we synthesized gold nanoparticles (AuNPs) using the stem of an Ayurvedic medicinal plant, Tinospora cordifolia, and studied the action of AuNPs against Pseudomonas aeruginosa PAO1 biofilm. The synthesized AuNPs were characterized by techniques such as ultravio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 46 publications
5
32
0
Order By: Relevance
“…Under identical conditions, Gram-positive MRSA cells were observed with significant structural damage along with tremendous bulging and deep cuts in cell membrane ( Figure 8 e,f), which indicated increased cytoplasmic granularity likely due to prompted interaction and internalization of LIV-AgNPs as compared to untreated cells ( Figure 8 d) [ 5 ]. Similarly, in the case of fungi, the LIV-AgNPs exposed C. albicans cells showed significant changes in native morphology such as deep pits in cells compared to untreated control ( Figure 8 h,i) as reported elsewhere [ 32 ]. Besides, Anuj et al [ 33 ] have demonstrated a steady release of Ag + from AgNPs and thus accumulated cations can destabilize cell membrane to combat with efflux-mediated drug resistance in Gram-negative bacteria.…”
Section: Resultssupporting
confidence: 84%
“…Under identical conditions, Gram-positive MRSA cells were observed with significant structural damage along with tremendous bulging and deep cuts in cell membrane ( Figure 8 e,f), which indicated increased cytoplasmic granularity likely due to prompted interaction and internalization of LIV-AgNPs as compared to untreated cells ( Figure 8 d) [ 5 ]. Similarly, in the case of fungi, the LIV-AgNPs exposed C. albicans cells showed significant changes in native morphology such as deep pits in cells compared to untreated control ( Figure 8 h,i) as reported elsewhere [ 32 ]. Besides, Anuj et al [ 33 ] have demonstrated a steady release of Ag + from AgNPs and thus accumulated cations can destabilize cell membrane to combat with efflux-mediated drug resistance in Gram-negative bacteria.…”
Section: Resultssupporting
confidence: 84%
“…The results proved the unexpected antibacterial power of Au NCs against Shigella . Au NCs are also expected to pass through the biofilms of Pseudomonas aeruginosa and Escherichia coli to kill pathogens, 51 , 52 potentially because tiny particles destroy the stability of the biofilm through some mechanisms. 53 We further explored the mechanism by focusing on ROS, which are essential for antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The ICP‐MS instrument was calibrated by standard solutions of Ti ions. In parallel, intracellular uptake of bare and GSE‐TiO 2 NPs in bacterial cells was evaluated qualitatively with TEM [54] . In detail, the P. aeruginosa and S. saprophyticus cells were incubated with 6.25 μg mL −1 of both TiO 2 NPs types for 24 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%